2022
DOI: 10.3389/fmicb.2022.801546
|View full text |Cite
|
Sign up to set email alerts
|

Rhizosphere Microbial Community Diversity and Function Analysis of Cut Chrysanthemum During Continuous Monocropping

Abstract: As an ornamental flower crop, the long-term continuous monocropping of cut chrysanthemum causes frequent occurrence of diseases, seriously affecting the quality of cut chrysanthemum. The rhizosphere microbial community plays an important role in maintaining the healthy growth of plants, whereas the composition and dynamics of rhizosphere microbial community under continuous monocropping of cut chrysanthemum have not been fully revealed. In this study, the Illumina MiSeq high-throughput sequencing platform was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 103 publications
4
22
0
Order By: Relevance
“…Past studies also suggested that prolonged CC could improve fungus biomass and decrease bacteria biomass, while long‐term CC of ginger might increase bacterial diversity, form bacteriostatic soil and inhibit soil sickness (Ma, Liao, et al, 2022; Yu et al, 2022). CC of chrysanthemum also promoted the fungal growth, and inhibited beneficial soil bacteria (Wang et al, 2022). Our findings indicated that CC of strawberry had resulted in a significant reduction in the diversity of bacteria and fungi, while the relative abundance of bacteria decreased more than that of fungi, leading to a significant reduction in the proportion of bacteria to fungi (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies also suggested that prolonged CC could improve fungus biomass and decrease bacteria biomass, while long‐term CC of ginger might increase bacterial diversity, form bacteriostatic soil and inhibit soil sickness (Ma, Liao, et al, 2022; Yu et al, 2022). CC of chrysanthemum also promoted the fungal growth, and inhibited beneficial soil bacteria (Wang et al, 2022). Our findings indicated that CC of strawberry had resulted in a significant reduction in the diversity of bacteria and fungi, while the relative abundance of bacteria decreased more than that of fungi, leading to a significant reduction in the proportion of bacteria to fungi (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The ecological functions of microbial assemblages are more resilient to perturbations than their structural changes, possibly due to the presence of functionally redundant species. Some guilds associated with plant pathogens in the soil rhizosphere could be significantly enriched by CC of cut chrysanthemum (Wang et al, 2022). CC also led to lead to changes in soil ecological function, weakening beneficial microbes and enhancing pathogenic fungi (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean values followed by different letter(s) in a column represent significant differences at p ≤ 0.05, LSD test reducing the proportion of some beneficial soil microbes, such as Bacillus, which are often negatively correlated with Fusarium [65]. This suggests that microbiota-optimized biofumigation may aid in improving crop productivity via soil nutrient enrichment and suppression of soil-borne pathogens and weeds [41,61,66].…”
Section: Soil Microbial Dynamics After Biofumigation Is Concentration...mentioning
confidence: 99%
“…According to Wu et al (2018), the populations of bacteria and fungi were signi cantly altered by CC of Rehmannia glutinosa, disrupting the balance between harmful and bene cial microbial communities in the soil. CC lowers the pH of the soil, promotes fungal growth, but suppresses the growth of actinomycetes and bacteria in the soil (Wang et al 2022). The study conducted by Li et al (2019) indicated an increase in soil fungus diversity over the 4-year period, while observing a decrease in the relative richness of Arthrobotrys within the CC.…”
Section: Introductionmentioning
confidence: 99%